Active bear, passive bull: a comparative analysis of active and passive investing during and bear market runs in South Africa - Naicker, Dylan (College of Accounting, 2025)
Purpose: This dissertation aims to evaluate whether actively managed portfolios achieve greater returns than passively managed portfolios. Previous studies relating to active versus passive investing have had mixed results. This study builds on the limitations of earlier studies by extending the time frame and eliminating survivorship bias. In addition, the analysis evaluated the South African markets' level of information efficiency using the efficient market hypothesis. Methodology: The portfolios used within the study are self-derived, and the weightings are rebalanced to allow new entrants to enter the market. This study will make use of a unit trust portfolio as the proxy for active investing and the portfolio of ETFs as the proxy for passive investing. Bull and bear markets were used in this study to determine distinct market conditions to measure the performance of the portfolios in different conditions. Bull and Bear markets are determined by comparing one standard deviation above and below the average market return using the CAPM model. The identified unit trust was further divided into its investing strategy (Value or non-Value investing strategies) and tested against the ETF portfolio to determine which investing strategy performs better. F-tests, t-tests and the Sharpe ratio was then used to analyse the returns of the portfolios during the identified market periods. Findings: It was found that during both market periods, the actively managed portfolio outperformed the passively managed portfolio, which is contrary to the findings of prior literature. These findings highlight that the South African market is weak and inefficient according to the efficient market hypothesis. Originality: This study built on the limitations of previous studies by first examining the portfolios over a more extended period to eliminate the shortcomings of previous research. This study offers an additional outlook into the performance of unit trusts by classifying them according to their investing nature, comprised of Value and non-Value funds, which will assist academics for further research and investors within the unit trust market.